The Degree of The Practice Of Mathematics Teachers For The Creative Thinking Skills In North Eastern Badia Schools - Alshrafat, Hussein Askar (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed at identifying the degree of the practice of mathematics teachers for the Creative thinking in north eastern Badia schools. To achieve the aim of the study, the researcher used the analytical descriptive design. The study sample consisted of (160) teachers who were selected randomly, using a questionnaire which consisted of (24) items after the confirmation of the validity and reliability.The study results showed that the degree of the practice of mathematics teachers for the creative thinking skills in Northeastern Badia schools was moderate and the most creative thinking skills of mathematics teachers are: elaboration skills significantly, and the least supporting flexibility skills moderately. The study also showed that there were statistically significant differences at the level of significance (α=0.05) due to the variable of experience in favor of teachers with (more than ten years). And there were no statistically significant differences at the level of significance (α=0.05) due to the variable of gender. In light of the consequences of the study, the researcher recommended a set of recommendations.
Keywords: Practicing; Mathematics teachers; The Creative thinking